El camino del grupo Raíces del Sudoeste en la transición agroecológica - Mediavilla Hernandez, María Clara; Gonzalez, Edgardo Gabriel; Braatz, Cristian (Universidad Nacional de Río Negro, 2023)
Ponencia y poster